Teknik Akupresur terhadap Kualitas Hidup pada Pasien Hemodialisis - Purwaningrum, Amin Rahmawati; Sultoni, Ahmad Mufid; Ximenes, Herminia; Sukartini, Tintin (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of acupressure in improving the quality of life of hemodialysis patients. The research method used in this study was a systematic review using the PICOT method by searching through the Pubmd, Science Direct, SAGE, SCOPUS, and Proquest databases to obtain nine articles discussing the effectiveness of acupressure in improving the quality of life of hemodialysis patients. The study's results revealed a positive impact of acupressure on enhancing the quality of life in patients with hemodialysis. The positive effects of acupressure include improving sleep quality and reducing pain intensity, depression, and anxiety. In conclusion, this acupressure therapy can help improve the quality of life experienced by hemodialysis patients. Keywords: Acupressure, Hemodialysis, Quality of Life (QOL)